8(x+8)=7z-42+z

Simple and best practice solution for 8(x+8)=7z-42+z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x+8)=7z-42+z equation:


Simplifying
8(x + 8) = 7z + -42 + z

Reorder the terms:
8(8 + x) = 7z + -42 + z
(8 * 8 + x * 8) = 7z + -42 + z
(64 + 8x) = 7z + -42 + z

Reorder the terms:
64 + 8x = -42 + 7z + z

Combine like terms: 7z + z = 8z
64 + 8x = -42 + 8z

Solving
64 + 8x = -42 + 8z

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-64' to each side of the equation.
64 + -64 + 8x = -42 + -64 + 8z

Combine like terms: 64 + -64 = 0
0 + 8x = -42 + -64 + 8z
8x = -42 + -64 + 8z

Combine like terms: -42 + -64 = -106
8x = -106 + 8z

Divide each side by '8'.
x = -13.25 + z

Simplifying
x = -13.25 + z

See similar equations:

| 12x^2-7x-4=0FActor | | 6x+5=21/x | | 1.5*2.25= | | 8=5-3x | | 2n-12=9n-63 | | 1+2x=2(2x+2)-3(1x-4) | | 12x^2-7x-4=0 | | 2.5*2.25= | | 15/3*2+3-4-3-7 | | (9-3i)-(2+i)= | | -6(7y-2)=31+9y | | 1+2x=2(x+2)-3(1x-4) | | -6=3t-36 | | 4t(6*6)/78t=567 | | 8n+32=2n-8 | | 4t(6*6)/78t= | | -25/24=-2/3-3/2n | | -310=5(7a-6) | | 31+8v=-1+7(3v-1) | | 11-(x/4)=-23 | | 9/4=f/28 | | 1+6a=-11+3a | | 8x+7=8+3x | | 19=-6+8(f-4) | | 265v^2+289=0 | | x-7=13-3x | | 8p-56=9p+10 | | rt-2n=yfort | | 3y(2y+1)+2y(y+6)=25 | | 9x^2-103x+328=0 | | 4x+3=7x-19 | | 3y(2y+1)+2y(y+6)= |

Equations solver categories